PENGARUH LEVERAGE, PROFITABILITAS, KOMISARIS INDEPENDEN DAN LIKUIDITAS TERHADAP TAX AVOIDANCE (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2012 - 2015) - Nirmalasari, 12.05.52.0219; Kartika, Andi (Students' Journal of Accounting and Banking, 2016)
This study aims to determine the effect of Leverage, Profitability, the Independent Commissioner and Liquidity of Tax Avoidances at manufacture companies which listed in the Indonesia Stock Exchange. The population on this research is all manufacture company in the Indonesia Stock Exchange in 2012 - 2015. The sampling technique used was purposive sampling. The analytical tool was used  is Multiple Regression Analysis. Partial results of this study show the profitability of significant negative effect on tax avoidances while variable leverage, independent commissioner and liquidity doesn’t affect the tax avoidances.  Keywords: Leverage,Profitability, Independent Comissioner, Liquidity and Tax Avoidance